Linguistic Folkloristic Analysis of the Work "Hotamnoma" - Abdumannatova Nafisa Abdumajit kizi (International Journal on Integrated Education, 2022)
In the article, the folk book "Hotamnoma" is analyzed from the linguo-folkloristic point of view. It describes the grammatical constructions used, doublets used in parallel, as well as the linguistic features of combinations with folk proverbs.